Hyperplasia and hypertrophy of pulmonary neuroepithelial bodies, presumed airway hypoxia sensors, in hypoxia-inducible factor prolyl hydroxylase-deficient mice - Pan J (Hypoxia, 2016)
Jie Pan,1,2 Tammie Bishop,3 Peter J Ratcliffe,3 Herman Yeger,1,2 Ernest Cutz1,2 1Division of Pathology, Department of Pediatric Laboratory Medicine, The Research Institute, The Hospital for Sick Children, 2Department of Laboratory Medicine and Pathobiology, University of Toronto, Toronto, ON, Canada; 3Nuffield Department of Medicine, Henry Wellcome Building for Molecular Physiology, University of Oxford, Oxford, UK Abstract: Pulmonary neuroepithelial bodies (NEBs), presumed polymodal airway sensors, consist of innervated clusters of amine (serotonin) and peptide-producing cells. While NEB responses to acute hypoxia are mediated by a membrane-bound O2 sensor complex, responses to sustained and/or chronic hypoxia involve a prolyl hydroxylase (PHD)–hypoxia-inducible factor-dependent mechanism. We have previously reported hyperplasia of NEBs in the lungs of Phd1–/– mice associated with enhanced serotonin secretion. Here we use a novel multilabel immunofluorescence method to assess NEB distribution, frequency, and size, together with the number and size of NEB cell nuclei, and to colocalize multiple cytoplasmic and nuclear epitopes in the lungs of Phd1–/–, Phd2+/–, and Phd3–/– mice and compare them with wild-type controls. To define the mechanisms of NEB cell hyperplasia, we used antibodies against Mash1 and Prox1 (neurogenic genes involved in NEB cell differentiation/maturation), hypoxia-inducible factor-1alpha, and the cell proliferation marker Ki67. Morphometric analysis of (% total lung area) immunostaining for synaptophysin (% synaptophysin), a cytoplasmic marker of NEB cells, was significantly increased in Phd1–/– and Phd3–/– mice compared to wild-type mice. In addition, NEB size and the number and size of NEB nuclei were also significantly increased, indicating that deficiency of Phds is associated with striking hyperplasia and hypertrophy of NEBs. In Phd2+/– mice, while mean % synaptophysin was comparable to wild-type controls, the NEB size was moderately increased, suggesting an effect even in heterozygotes. NEBs in all Phd-deficient mice showed increased expression of Mash1, Prox1, Ki67, and hypoxia-inducible factor-1alpha, in keeping with enhanced differentiation from precursor cells and a minor component of cell proliferation. Since the loss of PHD activity mimics chronic hypoxia, our data provide critical information on the potential role of PHDs in the pathobiology and mechanisms of NEB cell hyperplasia that is relevant to a number of pediatric lung disorders. Keywords: hypoxia, PHD, HIF, Mash1, neuroendocrine, pulmonary